Variability and correlations of synthetic chemicals in urine from a New York City-based cohort of pregnant women. (15th September 2022) - Gaylord, Abigail; Kannan, Kurunthachalam; Lakuleswaran, Mathusa; Zhu, Hongkai; Ghassabian, Akhgar; Jacobson, Melanie H.; Long, Sara; Liu, Hongxiu; Afanasyeva, Yelena; Kahn, Linda G.; Gu, Bo; Liu, Mengling; et al.
Abstract: Fetal exposure to environmental chemicals has been associated with adverse health outcomes in children and later into adulthood. While several studies have examined correlations and variability of non-persistent chemical exposures throughout pregnancy, many do not capture more recent exposures, particularly in New York City. Our goal was to characterize exposure to phthalates, bisphenols, polycyclic aromatic hydrocarbons, and organophosphate pesticides among pregnant women residing in New York City who enrolled in the New York University Children's Health and Environment Study (NYU CHES) between 2016 and 2018. We measured urinary chemical metabolite concentrations in 671 women at early, mid, and late pregnancy (median 10.8, 20.8, and 29.3 weeks, respectively). We calculated Spearman correlation coefficients among chemical concentrations at each measurement time point. We compared changes in population-level urinary metabolites at each stage using paired Wilcoxon signed-rank tests and calculated intraclass correlation coefficients (ICCs) to quantify intra-individual variability of metabolites across pregnancy. Geometric means and ICCs were compared to nine other pregnancy cohorts that recruited women in 2011 or later as well as nationally reported levels from women of child-bearing age. Compared with existing cohorts, women in NYU CHES had higher geometric means of organophosphate pesticides (Σdiethylphosphates = 28.7 nmol/g cr, Σdimethylphosphates = 57.3 nmol/g cr, Σdialkyl phosphates = 95.9 nmol/g cr), bisphenol S (0.56 μg/g cr), and 2-naphthalene (8.98 μg/g cr). Five PAH metabolites and two phthalate metabolites increased between early to mid and early to late pregnancy at the population level. Spearman correlation coefficients for chemical metabolites were generally below 0.50. Intra-individual exposures varied over time, as indicated by low ICCs (0.22–0.88, median = 0.38). However, these ICCs were often higher than those observed in other pregnancy cohorts. These results provide a general overview of the chemical metabolites measured in NYU CHES in comparison to other contemporary pregnancy cohorts and highlight directions for future studies. Graphical abstract: Image 1 Highlights: 671 pregnant women provided urine samples at early, mid, and late pregnancy. BPS, 2-NAP, and OP pesticide metabolites had higher concentrations than other cohorts. Five PAH metabolites and two phthalate metabolites increased over pregnancy. ICCs were generally similar or higher to comparable pregnancy cohorts.